Transcription termination and RNA degradation contribute to silencing of RNA polymerase II transcription within heterochromatin. - Vasiljeva, L; Kim, M; Terzi, N; Soares, L; Buratowski, S (2008)
Within the heterochromatin of budding yeast, RNA polymerase II (RNAPII) transcription is repressed by the Sir2 deacetylase. Although heterochromatic silencing is generally thought to be due to limited accessibility of the underlying DNA, there are several reports of RNAPII and basal transcription factors within silenced regions. Analysis of the rDNA array revealed cryptic RNAPII transcription within the "nontranscribed" spacer region. These transcripts are terminated by the Nrd1/Sen1 complex and degraded by the exosome. Mutations in this pathway lead to decreased silencing and dramatic chromatin changes in the rDNA locus. Interestingly, Nrd1 mutants also show higher levels of rDNA recombination, suggesting that the cryptic RNAPII transcription might have a physiological role in regulating rDNA copy number. The Nrd1/Sen1/exosome pathway also contributes to silencing at telomeric loci. These results suggest that silencing of heterochromatic genes in Saccharomyces cerevisiae occurs at both transcriptional and posttranscriptional levels.